Taking the high road : a metropolitan agenda for transportation reform - Katz, Bruce; Puentes, Robert (James A. Johnson metro series., 2005)
"Examines the challenges facing U.S. cities, suburbs, and metropolitan areas in light of the national debate on transportation policy--including finance, decisionmaking, access for the elderly and working poor, and congestion--and provides reform options that speak to leaders at the state, metropolitan, and local levels"--Provided by publisher